Functional characterization of a slow and tight-binding inhibitor of plasmin isolated from Russell's viper venom - Cheng, An-Chun; Tsai, Inn-Ho (Biochimica et biophysica acta, 2014)
Snake venoms are rich in Kunitz-type protease inhibitors that may have therapeutic applications. However, apart from trypsin or chymotrypsin inhibition, the functions of most of these inhibitors have not been elucidated. A detailed functional characterization of these inhibitors may lead to valuable drug candidates. A Kunitz-type protease inhibitor, named DrKIn-II, was tested for its ability to inhibit plasmin using various approaches such as far western blotting, kinetic analyses, fibrin plate assay and euglobulin clot lysis assay. In addition, the antifibrinolytic activity of DrKIn-II was demonstrated in vivo. DrKIn-II potently decreased the amidolytic activity of plasmin in a dose-dependent manner, with a global inhibition constant of 0.2nM. Inhibition kinetics demonstrated that the initial binding of DrKIn-II causes the enzyme to isomerize, leading to the formation of a much tighter enzyme-inhibitor complex. DrKIn-II also demonstrated antifibrinolytic activity in fibrin plate assay and significantly prolonged the lysis of the euglobulin clot. Screening of DrKIn-II against a panel of serine proteases indicated that plasmin is the preferential target of DrKIn-II. Furthermore, DrKIn-II treatment prevented the increase of FDP in coagulation-stimulated mice and significantly reduced the bleeding time in a murine tail bleeding model. DrKIn-II is a potent, slow and tight-binding plasmin inhibitor that demonstrates antifibrinolytic activity both in vitro and in vivo. This is the first in-depth functional characterization of a plasmin inhibitor from a viperid snake. The potent antifibrinolytic activity of DrKIn-II makes it a potential candidate for the development of novel antifibrinolytic agents. •A potent plasmin inhibitor from Russell's viper was functionally characterized.•DrKIn-II is a time-dependent and tight-binding inhibitor of plasmin.•Lysis of euglobulin clot was prolonged by DrKIn-II.•DrKIn-II prevented the increase of FDP and reduced the tail bleeding time in mice.•DrKIn-II's antifibrinolytic property has potential for therapeutic applications.